The wad of clay of mass m = 0.36 kg is initially moving with a horizontal velocity v1 = 6.0 m/s when it strikes and sticks to the initially stationary uniform slender bar of mass M = 4.3 kg and length L = 1.64 m. Determine the final angular velocity of the combined body and the x-component of the linear impulse applied to the body by the pivot O during the impact. The angular velocity is positive if counterclockwise, negative if clockwise. The impulse is positive if to the right, negative if to the left.

Respuesta :

Complete Question

The diagram for this question is shown on the first uploaded image

Answer:

The angular velocity is  [tex]w_2 = 0.8479 \ rad /s[/tex]

The linear impulse applied to the body by the pivot O during the impact is

      [tex]O_x \Delta t = 1.2153 N \cdot s[/tex]

Explanation:

The free body diagram of the image is shown on the second uploaded image

From the question we are told that

     The mass of the wad of clay is  [tex]m = 0.36 \ kg[/tex]

      Th velocity is  [tex]v_1 = 6.0 m/s[/tex]

      The mass of  slender bar [tex]M = 4.3 \ kg[/tex]

        The length is  [tex]L = 1.64 \ m[/tex]

From the diagram  the moment of inertia of the slender bar is

           [tex]I_o = \frac{1}{12} ML^2 + M(\frac{L}{6} )^2[/tex]

And the moment of inertia of the  slender bar and the clay sticked to it is

       [tex]I_T = \frac{1}{9} ML^2 + \frac{1}{9} mL^2[/tex]

            [tex]= \frac{1}{9} [M+m]L^2[/tex]

According to the law of conservation of angular momentum

    The initial angular momentum =  final angular momentum

The initial angular momentum of the clay is  

             [tex]P_i = mv_1 \frac{L}{3}[/tex]

The final angular momentum is

                   [tex]P_f = \frac{1}{9}[M + m] L^2 w_2[/tex]  

 So

       [tex]P_ i = P_f \equiv mv_1 \frac{L}{3} = \frac{1}{9} (M+ m )L^2 w_2[/tex]

So

        [tex]w_2 = \frac{3mv_1}{(M+m)L}[/tex]

From the diagram the center of gravity is calculated as

       [tex]r_G = \frac{M\frac{L}{6} + m \frac{L}{3} }{M+m}[/tex]

              [tex]= \frac{M + 2m }{6 (M + m)} L[/tex]

Now angular velocity along the x-axis

      [tex]-mv_1 + O_x \Delta t = -(M + m )r_G w_2[/tex]

     [tex]-mv_1 + O_x \Delta t = -(M +m ) \frac{M + 2m}{6 (M+ m)} L w_2[/tex]

    [tex]w_2 = \frac{3mv_1}{[M +m]L}[/tex]    

Where  [tex]O_x \Delta t[/tex]  is  linear impulse applied to the body by the pivot O

Substituting values

       [tex]w_2 = \frac{3 * 0.36 * 6}{[4.3 + 0.36] * 1.64}[/tex]

      [tex]w_2 = 0.8479 \ rad /s[/tex]

   Making  [tex]O_x \Delta t[/tex]  the subject of the formula

           [tex]O_x \Delta t =\frac{M}{2( M + m )} mv_1[/tex]

substituting value

          [tex]O_x \Delta t =\frac{4.3}{2( 4.2 + 0.36 )} (0.36)* (6.0)[/tex]

           [tex]O_x \Delta t = 1.2153 N \cdot s[/tex]

             

           

Ver imagen okpalawalter8
Ver imagen okpalawalter8